AB0189 Anti-Modified Protein Antibody Response Pattern Influences The Risk for Disease Relapse in Rheumatoid Arthritis Patients Tapering Disease Modifying Anti-Rheumatic Drugs. (15th July 2016) - Figueiredo, C.; Bang, H.; Cobra, J.F.; Englbrecht, M.; Hueber, A.J.; Haschka, J.; Manger, B.; Kleyer, A.; Reiser, M.; Finzel, S.; Tony, H.-P.; Kleinert, S.; et al.
Abstract : Background: Autoimmunity is still present in rheumatoid arthritis patients in sustained disease remission. In the absence of inflammation the pattern of autoimmunity against post-translationally modified proteins could potentially impact the course of disease of rheumatoid arthritis patients, espepcially their risk to experience relapse of disease when disease modifying anti-rheumatic drugs (DMARDs) are tapered or stopped Objectives: To perform a detailed analysis of the autoantibody response against post-translationally modified proteins in rheumatoid arthritis (RA) patients in sustained remission and to test whether its composition influences the risk for disease relapse when tapering DMARD therapy. Methods: Immune responses against 10 citrullinated, homocitrullinated/carbamylated and acetylated peptides, as well as unmodified vimentin (control) and cyclic citrullinated peptide 2 (CCP2) were tested in baseline serum samples from 94 patients of the RETRO study. Patients were classified according to the number of autoantibody reactivities (0–1/10, 2–5/10 and >5/10) or specificity groups (citrullination, carbamylation and acetylation; 0 to 3) and tested for their risk to develop relapses after DMARD tapering. Demographic and disease-specific parameters were included in multivariate logistic regression analysis for defining the role of autoantibodies in predicting relapse. Results: Patient varied in their anti-modified protein antibody response with the extremes from recognition of no (0/10) to all antigens (10/10). Antibodies against citrullinated vimentin (51%), acetylated ornithine (46%) and acetylated lysine (37%) were the most frequently observed sub-specificities. Relapse risk significantly (p=0.011) increased from 18% (0–1/10 reactivities) to 34% (2–5/10) and 55% (>5/10). With respect to specificity groups (0 to 3), relapse risk significantly (p=0.021) increased from 18% (no reactivity) to 28%, 36% and finally to 52% with one, two or three antibody specificity groups, respectively. Conclusions: The data suggest that the pattern of anti-modified protein antibody response determines the risk of disease relapse in RA patients tapering DMARD therapy. Disclosure of Interest: C. Figueiredo: None declared, H. Bang Employee of: Organtec Diagnostica, J. Cobra: None declared, M. Englbrecht: None declared, A. Hueber: None declared, J. Haschka: None declared, B. Manger: None declared, A. Kleyer: None declared, M. Reiser: None declared, S. Finzel: None declared, H.-P. Tony: None declared, S. Kleinert: None declared, J. Wendler: None declared, F. Schuch: None declared, M. Ronneberger: None declared, M. Feuchtenberger: None declared, M. Fleck: None declared, K. Manger: None declared, W. Ochs: None declared, M. Schmitt-Haendle: None declared, H.-M. Lorenz: None declared, H. Nuesslein: None declared, R. Alten: None declared, J. Henes: None declared, K. Krueger: None declared, J. Rech: None declared, G. Schett: None declared